A Study on Flow Boiling Heat Transfer of Mixtures in Channels - Chen Dongsheng; Shi Yumei (Zhileng xuebao, 2013)
Flow boiling phenomena of fluidic mixtures in channels exist widely in industry and is an important heat transfer method. This paper presents a state-of-the-art review on the theory development and achievements about flow boiling of mixtures in channels. And some correlations for prediction of the heat transfer coefficient in flow boiling of pure fluid or mixtures are introduced. The deficiencies on the present studies about flow boiling of mixtures are discussed, for example most of the correlations are not applicable for cryogenic fluids, the prediction precision and applicability of them are not satisfactory yet. Further study of heat transfer correlations on flow boiling is also discussed.